PENGARUH BIMBINGAN KELOMPOK TEHNIK MODELLING TERHADAP PERENCANAAN KARIR PESERTA DIDIK KELAS XI IPA SMAS 12 AL-WASHLIYAH PERBAUNGAN - Selfida Sunaria Purba; Ika Sandra Dewi; Dina Hidayati Hutasuhut; Nurul Azmi Saragih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the lack of group guidance services for career planning experienced by students, including not being able to determine plans after graduating from high school, not knowing about their interests, talents and abilities, so a study is needed entitled the influence of group guidance services on career planning for class XI IPA 1 students of SMAS 12 Al-Washliyah in the 2024/2025 academic year. This study aims to determine the effect of providing modeling technique group guidance services on career planning for class XI IPA students of SMAS 12 Al-Washliyah Perbaungan. This research is a quantitative research with an experimental type with a pre-experimental method of One Group Pre-test and Post-test Design. The subjects in this study were 10 students with low levels of career planning. This study focuses on the influence of modeling technique group guidance to improve students' career planning with the data collection technique used, namely a questionnaire. The data analysis method uses the Wilcoxon Signed Rank Test. Based on the results of data analysis using the Wilcoxon Signed Rank Test, the output value is Asymp. Sig. (2-tailed) of 0.005, sig. value 0.005 < 0.05 at a significance level of 5% or α = 0.05, it can be concluded that there is a significant difference in students' career planning before and after being given modeling technique group guidance services. These results indicate that modeling technique group guidance services can effectively improve the career planning of class XI IPA students of SMAS 12 Al-Washliyah Perbaungan.